2015
DOI: 10.1007/s10928-014-9402-0
|View full text |Cite
|
Sign up to set email alerts
|

Development of a physiologically based pharmacokinetic model for a domain antibody in mice using the two-pore theory

Abstract: Domain antibodies (dAbs) are the smallest antigen-binding fragments of immunoglobulins. To date, there is limited insight into the pharmacokinetics of dAbs, especially their distribution into tissues and elimination. The objective of this work was to develop a physiologically-based pharmacokinetic model to investigate the biodisposition of a non-specific dAb construct in mice. Following a single IV administration of 10 mg/kg dummy dAb protein to twenty four female mice, frequent blood samples were collected an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(51 citation statements)
references
References 28 publications
2
49
0
Order By: Relevance
“…In summary, we have demonstrated that the biologics PBPK framework we established using a series of inert tracer proteins in rodents 13 , 14 provided good to satisfactory extrapolation to humans without significant further parameterization. The resulting framework can be extended and adapted to more complex and clinically relevant scenarios for informative insight, as described for ibalizumab.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In summary, we have demonstrated that the biologics PBPK framework we established using a series of inert tracer proteins in rodents 13 , 14 provided good to satisfactory extrapolation to humans without significant further parameterization. The resulting framework can be extended and adapted to more complex and clinically relevant scenarios for informative insight, as described for ibalizumab.…”
Section: Discussionmentioning
confidence: 90%
“…In the case of proteins, the most flexible approach is often described in terms of two-pore hypothesis proposed by Rippe and Haraldsson 12 where extravasation is linked to the lymph flow and treated as a filtration-diffusion process taking place at the paracellular vascular pores. Previously we showed in theory and practice that the filtration and diffusion-driven fluxes can be treated as linear functions of the lymph flow rate in such systems, 13 and followed up with an extensive study in mice and rats where the same framework was applied to a number of different biologics to estimate the organ-specific fractional lymph flow rates as the only empirically fitted global parameters. 14 …”
Section: Introductionmentioning
confidence: 99%
“…The ratio does not describe a parallel pipe configuration nor does it represent a known physical. Other PBTK models [ 17,18 ] utilize Qorgan_blood/Vorgan_blood_volume, which is the residence time for every traverse through the organ. In the ETH model, the extremes of long residence times (lower flow rate, larger organ blood volume) and short ones (higher flow rate, smaller organ blood volume) are not fully expressed, and of note relative to argyria, the rat skin compartment is at the lower flowrate/larger volume extreme (see Table S1 of ref.…”
Section: Materials Model Discussion Of Bachler Et Almentioning
confidence: 99%
“…The aim of the current work is to extend the established PBPK model in PK-Sim [ 33 36 ] which was designed for small molecule drugs, to allow simulation of macromolecules such as protein therapeutics in one comprehensive pharmacokinetic modeling framework. The current implementation of the model replaces the unpublished generic protein PBPK model available in PK-Sim since version 4.2 providing an updated parameterization using new experimental data [ 29 ] and an explicit representation of drug–FcRn binding. The model becomes part of the open source Open Systems Pharmacology Suite ( www.open-systems-pharmacology.org ).…”
Section: Introductionmentioning
confidence: 99%